2018
DOI: 10.31224/osf.io/w8vng
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Natural Strategies for Bio-Inspired Fault Adaptive Systems Design

Abstract: Fault adaptive design seeks to find the principles and properties that enable robustness, reliability and resilience to implement those features into engineering products. In nature, this characteristic of adaptability is the fundamental trait that enables survival. Utilizing adaption strategy is a new area of research exploration for bio-inspired design. In this paper we introduce a tool for bio-inspired design for fault adaption. Further we discuss insights from using this tool in a undergraduate design expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Much research has been done so far to study ways of designing complex systems. For instance, Arroyo et al (2018) came up with a bio-inspired, binary-tree-based method for complex system design with fault adaptiveness. The binary-tree branches indicate how organisms achieve adaptive behaviors.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research has been done so far to study ways of designing complex systems. For instance, Arroyo et al (2018) came up with a bio-inspired, binary-tree-based method for complex system design with fault adaptiveness. The binary-tree branches indicate how organisms achieve adaptive behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…The binary-tree branches indicate how organisms achieve adaptive behaviors. Their results show that a strategy-based method can aid designers with innovative analogies, which is useful in providing needed details in design applications (Arroyo et al , 2018). Königseder and Shea (2016) analyzed various strategies of rule applications in two design synthesis case studies: bicycle frame synthesis and gearbox synthesis, and they found that the effectiveness of each strategy depends on the task scenario.…”
Section: Related Workmentioning
confidence: 99%
“…Adaptive System Design tool, etc., to also incorporate possible evolutionary constraints, in order to arrive at not only the best possible BID solution, but also at identifying potentials for further optimization [25,31,[88][89][90][91].…”
Section: Evomimetic Design Thinkingmentioning
confidence: 99%